Coffee, Cookies and Cards: The Use of Visuals and Materiality to Reproduce and Transform Masculinity in Dutch Social Work Interventions - Iris van Huis; Marleen van der Haar (Gender a Výzkum, 2015)
In what way do gender-specific interventions aimed at marginalised men reproduce and transform masculinities, and what kind of masculinity do social professionals, who carry out these projects, work with? This paper analyses how visual materials, spaces and artefacts enable professionals to deal with masculinity and gender-equality issues when working with men whom they assume hold traditional views on masculinity and gender roles. A three-year study of semi-public interventions that worked on individual empowerment, participation and gender equality with marginalised men in the Netherlands revealed that the professionals found it difficult to raise gender-equality issues. In contrast to the other project goals of individual empowerment and participation, gender-equality issues created a discomfort. The authors also discovered that gender equality in most cases was dealt with in more subtle ways than the issues of individual empowerment and participation. In this context, professionals worked with an ideal version of what the ‘new’ masculinity of the participants would look like, which we labelled ‘pacified masculinity’. The paper empirically shows how social professionals benefit from the use of space, images and artefacts to break down rigid gender roles and potentially enable men to construct other versions of masculine identity. Moreover, we argue that visuals and materiality create room for a reflection on the role of men in women’s emancipation.